Digital Marketing Strategy to Increase Brand Awareness of PT Global Service Indonesia - Taufiq, Fariz Fahrezi; Rozci, Fatchur (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
The ability to understand consumer behaviour in the digital age is a very important strategy to achieve competitive advantage. Digital marketing or marketing that uses electronic devices or the internet, provides opportunities for consumers to find information about what positions they are interested in, and obtain testimonials from other consumers about their experiences after following the employee recruitment process. The purpose of this paper is to explain the digital marketing strategy of PT Global Service Indonesia to increase brand awareness, with a special focus on the role and contribution of MSIB interns in the process. This study will evaluate the effectiveness of various digital marketing tactics implemented, challenges, and obstacles faced in their implementation. The method used in this paper is qualitative data analysis based on the constructivist paradigm. Results show that there was a significant increase in the followers and interest of job seekers from April to June 2024.